Analisis Dampak Perubahan Tarif PPN di Indonesia Menggunakan Model Computable General Equilibrium (CGE) - Iman Akhadi; Umar Issa Zubaidi (Media Bisnis, 2025)
This study aims to analyze the impact of the Value Added Tax (VAT) rate increase policy from 11% to 12% on the Indonesian economy, particularly on economic growth, household consumption, and private consumption. The study was conducted using a static Computable General Equilibrium (CGE) Model based on the 2022 Social Accounting Matrix (SAM), adopting the RIAPA model framework developed by IFPRI to simulate fiscal policy. The simulation was conducted through two scenarios: scenario I, which applies a full VAT rate increase to all taxable goods and services, and scenario II, which applies a VAT rate increase with a differentiation scheme according to PMK No. 131/2024, which is only imposed on luxury goods that are subject to PPnBM. The results of the study indicate that the first scenario has a contractionary impact on the economy, with a decrease in GDP of -0.154%, a decrease in household consumption of -0.550%, and a decrease in private consumption of -0.431% as a result of the increase in prices of goods and services, which ultimately suppresses consumer purchasing power. In contrast, the second scenario produces a more neutral impact on economic growth, household and private consumption, while still increasing state revenue, with an insignificant effect on economic growth of -1.05e-5, on household consumption of 5.03e-5, and on private consumption of 2.01e-6. This finding confirms that the tariff differentiation policy is more effective in maintaining a balance between optimizing state revenue and protecting public purchasing power.